History of Policing, Crime, Disorder, Punishment - Joyce, Peter; Laverick, Wendy (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This engaging textbook provides a broad and unique coverage of the key historical events that shaped ideas in criminology, criminal justice and policing from the late seventeenth century to the early twenty-first century. It vividly illustrates the multi-disciplinary nature of criminology and penology by providing important insights into the social and political issues that shaped the development and operations of the criminal justice system and its responses to both crime and disorder. Using key text boxes, this book highlights key people, theorists, foundational principles and events throughout. Part One discusses the nature of crime and forms of punishment between 1689 and 1750 and the penological concerns regarding the aims of punishment. Part Two focuses on crime and disorder between 1750 and 1850, examining the impact of urbanization on criminal activity and it considers the background and state responses to key episodes of public disorder. Part Three covers the development of policing 1689-1856 and the contribution to policing made by reformers and the implementation of police reform. Part Four deals with a number of issues affecting crime and punishment between 1850 and 1920 including episodes such as Irish Home Rule within the context of 'high policing'. It evaluates changes to the nature and role of prisons that occurred in this period. This student-friendly book contains end of chapter questions which summarise and enable further discussion. Peter Joyce is Visiting Professor in Criminology at Wrexham University, UK. He is widely published in Criminology and Politics, specializing in policing and the policing of protest. He co-authored (with Wendy Laverick) a second edition of Policing: Development and Contemporary Practice (2021). Wendy Laverick is Senior Lecturer in Policing and Criminology at the University of Hull, UK. She has an international research profile on transnational crime, hate crime and gender and policing scholarship and is the author of Global Injustice and Crime Control (2016). She co-authored (with Peter Joyce) Racial and Religious Hate Crime: The UK from 1945 to Brexit (Palgrave Macmillan, 2019).
Part One: Crime and Punishment, 1689-1750. 1. Introduction -- 2. The Character and Nature of Crime in the Early Eighteenth Century -- 3. Urban Policing -- Part Two: Crime and Disorder 1750 - 1850 - 4. Crowd Disorders 1750 - 1800 -- 5. Public Disorder and the State's Response 1800-1850 -- 6. Reform of Prisons, the Penal Code and Legal System -- Part Three: The Development of Professional Policing from the Late Eighteenth Century - 1856 - 7. Police Reformers and Police Reform in the Late Eighteenth and Early Nineteenth Centuries -- 8. The Development of Professional Policing in London -- 9. The Development of Professional Policing in England and Wales (Outside of London) -- Part 4: Crime and Punishment 1850 - 1920 - 10. Issues Affecting Policing 1850-1920 -- 11. Crime and Disorder 1850 - 1920 -- 12. Responses to Crime.
Keywords: Criminology -- History; Criminology; Corrections; Punishment; Crime -- Sociological aspects; Law -- History; Europe -- History; History of Criminology; Crime Control and Security; Prison and Punishment; Crime and Society; Legal History; European History